Migration of Health Workers in COVID-19 Conditions - Emília KRAJŇÁKOVÁ; Jaroslav VYHNIČKA (Communications of International Proceedings, 2020)
In the current situation associated with COVID-19, radical measures concerning social distance and mobility are increasingly being introduced. Borders are closing, but life in hospitals is experiencing trials for which no one has been sufficiently prepared. Infected people who need health care come to the hospitals. At the same time, to protect those who are in the hospital due to other problems and not to put them at risk. We also encounter a number of problems associated with the provision of medical supplies and equipment, the organization of newly established health departments, the adoption of adequate legislative standards, etc. We are witnessing the emergence of cohesion between peoples and countries and, at the same time, egoism at various levels. These events develop in conditions of relatively intensive migration of health workers. Its causes are mainly related to differences in working conditions and remuneration of health workers in individual countries and their shortage. The occurrence of the coronavirus epidemic has updated and multiplied the need for health professionals around the world. At the same time, from a common point of view, it is not clear what is happening with the migration of health professionals in the conditions of COVID-19. Several events and measures taken in individual countries should strengthen the migration of health professionals, while others should dampen and even suspend or re-emigrate (return home). What is actually happening with the migration flows of health workers, especially in European countries, is the subject of analyzes and findings of the study.
Keywords: Migration; COVID-19; Health Workers.